Research on thermal infrared anomaly characteristics of moderate strong earthquakes in northeast China - Li, Mengying; Zhang, Zhihong; Yang, Shichao; Kong, Xiangrui; Jiao, Mingruo (Frontiers in Earth Science, 2023)
Domestic and foreign scholars have made a good summary of an earthquake in a certain area, it is of great theoretical and practical significance to carry out experimental research on satellite thermal infrared anomaly. As a short-term and imminent precursor of earthquakes, satellite thermal infrared anomaly has been confirmed by dozens of moderate and strong earthquakes. In this paper, using the daily brightness temperature data of China Geostationary Meteorological Satellite FY-2C/E/G from January 2006 to May 2019, wavelet transform and relative power spectrum methods are used to identify the brightness temperature difference before deep and shallow earthquakes in the study area. And we try to explore the characteristics of infrared thermal radiation anomaly changes before deep and shallow earthquakes in Northeast China, and carry out anomaly extraction and data analysis. The results show that thermal infrared anomalies occurred in the vicinity of the epicenter about 1 to 2 months before 5 earthquakes in the twenty selected earthquake cases, the anomaly amplitude was up to 7-20 times, and the anomaly duration was about 3 months. Among them, the two earthquakes occurred in Songyuan area have obvious infrared radiation anomaly characteristics before the earthquake, and the regional geological structure is very typical. Therefore, we analyzed the expression characteristics of the brightness temperature before the two earthquakes. And the results showed that: Before the MS4.9 earthquake on July 23,2017 and the MS5.7 earthquake on May 28, 2018,the anomalies have gradually expanded along the Yilan-Yitong fault and Mishan-Dunhua fault zone. Both anomalies existed in the eastern edge of the Songliao Basin, and the epicenter of the earthquake was not in the anomaly area. The anomaly was not obvious before the MS5.1 earthquake on May 18,2019.It's a possibility that greenhouse gases have been released in the greatest amount in the basin before and after the previous two earthquakes. Based on the above understanding, we have studied more researches and analysis deeply on these earthquakes. In this paper, we mainly study the expression characteristics of the brightness temperature before the Ms4.9 and Ms5.7 earthquake in Songyuan area. The other three earthquakes have similar infrared anomaly characteristics.